2020
DOI: 10.3389/fphys.2020.00038
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in High-Intensity Interval Training–Are HIIT Protocols Interchangeable Between Females and Males?

Abstract: Background: High-intensity interval training (HIIT) is a well-established training modality to improve aerobic and anaerobic capacity. However, sex-specific aspects of different HIIT protocols are incompletely understood. This study aimed to compare two HIIT protocols with different recovery periods in moderately trained females and males and to investigate whether sex affects high-intensity running speed and speed decrement. Methods: Fifty moderately trained participants (30 females and 20 males) performed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 43 publications
3
37
0
Order By: Relevance
“…In this sense, although the HIIT all-out format is accepted in the scientific literature, taekwondo athletes may have underestimated the intensity of the work performed; (ii) the lack of control of dietary habits that could have influenced the reported changes in body composition; (iii) the lack of progression of the training load applied in HIIT; (iv) the evaluation by bioimpedance, which could have overestimated the body composition; and (v) the small number of athletes analysed. In addition, potential biases that could have influenced the results of this study include the following: (i) the variability of the response according to the sex of the athletes [ 49 , 50 , 51 ]; (ii) the absence of analysis and subsequent distribution of the athletes according to their biological age [ 52 , 53 ]; (iii) the variation of physical performance according to the time of day [ 54 ]; and (vi) the possible variability of the body composition due to the use of bioimpedance [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, although the HIIT all-out format is accepted in the scientific literature, taekwondo athletes may have underestimated the intensity of the work performed; (ii) the lack of control of dietary habits that could have influenced the reported changes in body composition; (iii) the lack of progression of the training load applied in HIIT; (iv) the evaluation by bioimpedance, which could have overestimated the body composition; and (v) the small number of athletes analysed. In addition, potential biases that could have influenced the results of this study include the following: (i) the variability of the response according to the sex of the athletes [ 49 , 50 , 51 ]; (ii) the absence of analysis and subsequent distribution of the athletes according to their biological age [ 52 , 53 ]; (iii) the variation of physical performance according to the time of day [ 54 ]; and (vi) the possible variability of the body composition due to the use of bioimpedance [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that females require less rest between intense interval exertions for adequate metabolic recovery; if standard training recommendations that are based predominately on male research are applied to both sexes, females might not receive an optimal stimulus for adaptation. Indeed, a recent study investigated whether manipulation of the rest period duration affects the adaptation to an interval training programme in males and females (Schmitz et al., 2020). The authors demonstrated a reduced training effect in female participants when rest periods were extended from 30 to 180 s, with no such effect in males.…”
Section: The Acute and Chronic Implications Of Sex Differencesmentioning
confidence: 99%
“…HIIT protocols from studies only performed with men are commonly adapted for women. This might be erroneous as the present results and previous studies have indicated that sex-dependent and anthropometric and physiological differences between females and males might significantly affect recovery following repeated high-intensity exercise and thus can affect training response [ 36 , 37 ]. During repeated bouts of exercise women, may be more resistant to fatigue and have a greater ability to recover metabolically, but they have slower heart rates and subjective recovery.…”
Section: Resultsmentioning
confidence: 65%